Pengaruh Job crafting terhadap Workplace Well-Being pada Karyawan di Kota Bandung - Irfan Nasiruddin Khairi; Sita Rositawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. Since the COVID-19 pandemic, employees have become working from home or WFH, working from home has created a separate burden for employees, which has an impact on employee happiness. According to the survey results during WFH, the level of employee happiness decreased significantly. The concept of happiness has the same meaning as the concept of well-being. Well-being at work is a feeling of satisfaction felt by employees as a whole related to their work. Workplace well-being is influenced by the balance between job demand and job resources. Efforts made by employees in balancing the demands of work and work resources are called job crafting. This study aims to determine the effect of job crafting on employee welfare in the city of Bandung. The hypothesis proposed in this study is that job crafting has a major effect on work welfare for employees in the city of Bandung. To test this research, this study uses a quantitative approach with multiple regression analysis techniques. The population in this study were employees in the city of Bandung, amounting to 387 people. The researcher uses the Workplace well-being Index from Page which has been modified by Maulidina (2020) and the Job crafting Scale from Tims, Bakker and Derk which has been translated into Indonesian by Sutisna (2020). The population in this study amounted to 387 employees. The results of this study indicate that job crafting has a large and significant effect of 56.1%. The dimensions that have a big and significant impact are only the dimensions of increasing structural work resources and decreasing job demands that are hampering. Abstrak. Sejak terjadinya pandemi covid-19 karyawan menjadi bekerja dari rumah atau WFH, bekerja dari rumah menimbulkan beban tersendiri bagi karyawan, sehingga berdampak pada kebahagiaan karyawan. Menurut hasil survey pada saat WFH, tingkat kebahagiaan karyawan menurun signifikan. Konsep kebahagiaan memiliki arti yang sama deng konsep kesejahteraan. Kesejahteraan di tepat kerja atau workplace well-being merupakan perasaan puas yang dirasakan karyawan secara keseluruhan terkait pekerjaannya. Workplace well-being dipengaruhi oleh adanya keseimbangan antara job demand dan job resources. Upaya yang dilakukan karyawan dalam menyeimbangkan job demand dan job resources disebut job crafting. Penelitian ini bertujuan untuk mengetahui pengaruh job crafting terhadap workplace well-being pada karyawan di Kota Bandung. Hipotesis yang diajukan dalam penelitian ini adalah job crafting memiliki pengaruh yang besar terhadap workplace well-being pada karyawan di Kota Bandung. Untuk menguji penelitian ini, Penelitian ini menggunakan pendekatan kuantitatif dengan teknik analisis regresi berganda. Populasi penelitian ini adalah karyawan di Kota Bandung yang berjulmah 387 orang. Peneliti menggunakan alat ukur Workplace well-being Index dari Page, yang telah dimodifikasi oleh Maulidina (2020) dan Job crafting Scale dari Tims, Bakker dan Derk, yang telah dialih bahasakan kedalam bahasa Indonesia oleh Sutisna (2020). Populasi dalam penelitian ini sebesar 387 karyawan. Hasil penelitian ini menunjukan job crafting memberikan pengaruh yang besar dan signifikan sebesar 56,1%. Dimensi yang memberikan pengaruh yang besar dan signifikan hanyalah dimensi increasing structural job resources dan decreasing hindering job demand.